The Definition of the Term "Orthogeriatric Infection" for Periprosthetic Joint Infections. (22nd June 2022) - Walter, Nike; Rupp, Markus; Bärtl, Susanne; Uecker, Claus; Alt, Volker
Introduction: In the background of the aging population, an increase of geriatric patients with specific age-related co-morbidities has already been seen over the years for proximal femur fractures in orthopaedic surgery as well as other medical disciplines. However, the geriatric aspect has not been well recognized in periprosthetic joint infection (PJI) patients so far. Therefore, this paper seeks to provide an overview on the co-morbidities of PJI patients with respect to the definition of geriatric patients. Material and methods: In this single-center retrospective study, patients treated between 2007 and 2020 for PJI were included (n = 255). Patients were defined as geriatric according to the consensus definition criteria of the Federal Working Group of Clinical Geriatric Facilities e.V., the German Society for Geriatrics e.V. and the German Society for Gerontology and Geriatrics e.V. based on age (≤70 years), geriatric multimorbidity and the Barthel index (≤30). Results: Applying the criteria defined 184 of the 255 (72.2%) PJI patients as geriatric infection patients. Regarding geriatric comorbidity, incontinence was most prevalent (38.1%), followed by immobility (25.6%). Comparing the geriatric infection patients with those classified as non-geriatric (n = 71) revealed that geriatric patients had a longer hospital stay and spent more days in the intensive care unit (ICU). Also, the amputation rate and the 5-year mortality rate was significantly increased (n = 15, 8.2% vs n = 1, 1.4%, P = .007 and n = 24, 13.0% vs n = 5, 7.0%, P = .005). The Barthel index showed a significant correlation with mortality ( r = −.22, P = .011). Discussion: We propose to use the term orthogeriatric infection patients in those cases in order to focus treatment not only on the orthopaedic infections but also on the important geriatric aspects. Conclusion: The inclusion of geriatric physicians into the multidisciplinary team approach for PJI patients might be beneficial.